A Study on the Purchase Behavior and Cosmetic Consumption Pattern among Young Females in Delhi and NCR - Junaid, Abdullah Bin; ., Faheem Ahmed (Journal of Social and Development Sciences, 2013)
This study was carried out to examine consumption behaviour of young females and their attitudes towards cosmetics in Delhi/NCR. This research focuses on the different marketing variables affects the female cosmetic consumption as well as their decision making process for purchasing the cosmetic products. This study also explains to some extent the influence of customer decision making process in purchasing the dermaceutical products in Delhi/NCR. The target sample was between the age group of 15 years to 35 years females and those who are living in Delhi/NCR. This age group fall under the category of young generation and they can be categories in the Millennials (those who are born after 1980). This study may also help various cosmetic companies to formulate their strategies for marketing the cosmetic products. Primary data was obtained through questionnaire. The results were analyzed through SPSS version 16.